Nanopartículas poliméricas funcionalizadas con dermatán sulfato para la distribución específica de compuestos bioactivos - Blachman, Agustín (2024)
The incidence of colorectal cancer (CRC) has increased among people under 40,\nattributed to lifestyle changes and the lack of preventive screenings. 5-Fluorouracil (5-\nFU) remains the standard treatment; however, its prolonged use is limited by the\nemergence of resistance, influenced by the presence of cancer stem cells (CSCs) and the\nactivation of signaling pathways such as NF?B. The CD44 receptor plays a crucial role in\nCRC, being considered a CSCs marker. This study aims to formulate nanoparticles (NPs)\nof dermatan sulfate (DS) and chitosan, loaded with the anti-inflammatory tripeptide IRW\nand 5-FU, to achieve their selective distribution. These formulations selectively interact\nwith tumor cells, CSCs, and endothelial cells (ECs) via DS and CD44. IRW loaded NPs\nsensitize tumor cells to 5-FU treatment by inhibiting the NF?B pathway, increasing its\neffectiveness, and selectively targeting injured ECs, reversing their activation.\nAdditionally, 5-FU NPs effectively deliver the drug to tumor cells, allowing the drug to\nexert its antitumor function. In conclusion, this work presents an innovative approach\nto improving CRC treatment, targeting both tumor cells and CSCs, offering new\nstrategies to address 5-FU tolerance and its side effects.